2017
DOI: 10.18805/ijar.b-3305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified housing system on physiological parameters of Murrah buffaloes during autumn and winter season

Abstract: The aim of this study was to assess the effect of modified housing system on physiological parameters like rectal temperature, skin temperature, plasma cortisol level, respiration rate and pulse rate (counts/min) of Murrah buffaloes during autumn and winter seasons. A total of 14 lactating Murrah buffaloes were randomly selected and divided into two groups, on the basis of age, body weight (BW) and parity (P). T 1 =First group (n=7; BW=544.86kg; P=2.14) of buffaloes was housed under existing loose housing syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Joshi and Kamboj (2014) reported that in winter, rectal temperature in control and treatment group of animals was 38.29±0.04 0 C (100.92 0 F) and 38.00±0.05 0 C (100.40 0 F) respectively. Kumar et al (2017) also reported that the rectal temperature of Murrah Buffaloes , during autumn and winter season the mean were significantly (P<0.05) lower in buffaloes housed under modified shed as compared to existing shed.But in the hotdry summer rectal temperature in the control group was founded to be 38.67±0.09 0 C (101.60 0 F) and for treatment group it was 38.48±0.07 0 C (101.27 0 F). The rectal temperature of control group of animals was significantly higher (P<0.05) from treatment group of animals.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Joshi and Kamboj (2014) reported that in winter, rectal temperature in control and treatment group of animals was 38.29±0.04 0 C (100.92 0 F) and 38.00±0.05 0 C (100.40 0 F) respectively. Kumar et al (2017) also reported that the rectal temperature of Murrah Buffaloes , during autumn and winter season the mean were significantly (P<0.05) lower in buffaloes housed under modified shed as compared to existing shed.But in the hotdry summer rectal temperature in the control group was founded to be 38.67±0.09 0 C (101.60 0 F) and for treatment group it was 38.48±0.07 0 C (101.27 0 F). The rectal temperature of control group of animals was significantly higher (P<0.05) from treatment group of animals.…”
mentioning
confidence: 80%
“…respectively. Kumar et al (2017) reported that the pulse rate during autumn and winter season were significantly (P<0.01)lower in buffaloes housed under modified shed as compared to existing shed. Joshi and Kamboj (2014) observed that in winter pulse rate in treatment 76.86±0.90 counts/minute group of animals was significantly higher (P<0.05) than control 72.99±0.19 counts/minute.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Replacing the flooring of resting areas for these ruminants with more comfortable flooring could be an effective first approach to improving their welfare conditions, as has already been demonstrated in other case studies involving cows [44][45][46][47]. Indeed, improving the living conditions of buffaloes translates into numerous benefits, including a reduction in the occurrence of joint diseases, an increase in milk yield and milk quality, and an improvement in well-being as a result of providing hygienic resting spaces [36][37][38]48,49].…”
Section: Introductionmentioning
confidence: 90%